INTERVIEWING DR. BILL COPE AND DR. MARY KALANTZIS: NEW TIMES, NEW LEARNING / Entrevistando Dr. Bill Cope e Drª. Mary Kalantzis: novos tempos, novo ensino - Cope, Bill; Kalantzis, Mary; Fernandes, Alessandra Coutinho (Pensares em Revista, 2018)
Alessandra Coutinho Fernandes (UFPR) interviews Cope and Kalantzis, mainly known for having been members of The New London Group – a group of researchers who met back in 1994, in the city of New London in the USA, to discuss literacies and the future of education.